Lexical Features of New-Zealand English - Salauatova, A. (KAZGUU Liberal Arts Digest Volume 5. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2023)
The focus of this research is on investigating the New-Zealand English and identifying some lexical features. It will be conducted in order to see to what extend the vocabulary of New Zealanders differ from other English speaking countries and what is the reason of such phenomenon. While studying the subject, history of New Zealand and its development was taken into account for better understanding of the language peculiarities. By the end of the research, it will be clear that New Zealanders have unique vocabulary, that might be difficult to understand for people from other countries. However, it was formed mostly under the influence of Australian English, native people use a lot of Australian slang words in particular.
Keywords: New Zealand English Lexical features Lexical variation Vocabulary comparison, English language differences, Slang in New Zealand English, Acronyms in New Zealand English, Language identity